Dietary Patterns During Pregnancy and the Risk of Postpartum Depression - MR Maracy; S Iranpour; A Esmaillzadeh; GHR Kheirabadi (مجله اپیدمیولوژی ایران, 2014)
Background & Objectives: Since the human diet is a combination of different foods and that this combination will affect the body differently from when these foods are received separately, the evaluation of dietary patterns is of great importance. The primary aim of this study was to examine the association between dietary patterns during pregnancy and postpartum depression.   Methods : This population-based, cross-sectional study was conducted on 771 women who attended the Ardabil's health care network. This study was carried out in a period of 4 months. In this study, systematic random sampling was used. Dietary data was collected using the Willett-format Dish-based 106 items Semi-quantitative Food Frequency Questionnaire (DS-FFQ) which was designed and validated specifically for Iranian adults. Dietary patterns were identified through exploratory factor analysis based on 34 predefined food groups. In the present study, individuals who obtained a rating of 13 or higher were considered to be suffering from postpartum depression. Logistic regression was used to estimate OR and 95% CI for postpartum depression in each quartile of patterns.   Results : In the present study, three dietary patterns were identified: mixed dietary pattern, semi-healthy dietary pattern, and fruits and vegetables dietary pattern. The last one was significantly associated with a reduced risk of postpartum depression.   Conclusion : The findings show that a diet of fruits and vegetables during pregnancy is associated with a reduction in the risk of PPD. Additional studies are recommended to confirm these finding.